The Mediating Role of Mindfulness in the Effect of a Prevention Program on Anxiety and Perfectionism in College Students - Lamarre, Cynthia; Marcotte, Diane (Canadian Journal of Counselling and Psychotherapy, 2021)
College students report experiencing anxiety that affects their academic performance, and requests for psychological assistance are increasing among these students. This study was designed to assess the impact of a prevention program on anxiety, perfectionism, and the mediating role of mindfulness on student anxiety and perfectionism after students participated in the program. The results show that program participants (n = 22) reported less anxiety than those in a comparison group (n = 19) and that these effects were maintained over time. Effects on mindfulness, perfectionism, and the mediating effect have not been confirmed. While this study validates the program’s effect on anxiety, mindfulness has not been identified as an essential program component. Limits on the difficulty of measuring mindfulness are discussed.